Drosophila insulin‐like peptides: from expression to functions – a review. Issue 2 (27th October 2020) - Semaniuk, Uliana; Piskovatska, Veronika; Strilbytska, Olha; Strutynska, Tetiana; Burdyliuk, Nadia; Vaiserman, Alexander; Bubalo, Volodymyr; Storey, Kenneth B.; Lushchak, Oleh
Abstract: Insulin‐like peptides (ILPs) belong to the insulin superfamily and act as hormones, neuromediators, and growth factors during the post‐embryonic life‐cycle stages of insects. These peptides are encoded by different genes in various species. In the genus Drosophila, eight peptides are known, seven of which are likely to bind the Drosophila insulin receptor, whereas DILP8 is a known ligand of the Lgr3 receptor. Binding of DILPs 1‐7 to receptors leads to activation of intracellular proteins related to the conserved insulin/IGF (insulin‐like growth factors) signaling pathway. The insulin pathway acts within a complex physiological regulatory network involved in the coordination of development, growth, behavior, metabolism, lifespan, and cognitive functions in insects. The current review summarizes recent data about the structure and function of ILPs in fruit flies. The role of environmental factors and genetic manipulations in modulating the functions of DILPs and their association with lifespan and metabolism of Drosophila are assessed. Further investigation and identification of pharmacological or biotechnological interventions that may decrease insulin/IGF signaling could be a highly promising approach for extension of human health span and longevity. Abstract : This review summarizes the recent knowledge about the insulin‐like peptides (DILPs) in fruit flies (Diptera: Drosophilidae). Sites of expression and main functions in the regulation of a range of traits are described, and the role of environmental factors and genetic manipulation in modulating the functions of DILPs and their association with lifespan and metabolism are assessed. Further investigation and identification of pharmacological or biotechnological interventions that may decrease insulin/IGF signaling could be informative for extension of human health span and longevity.